2017
DOI: 10.13075/mp.5893.00519
|View full text |Cite
|
Sign up to set email alerts
|

ERCP procedures as a source of radiation risk to a single gastroenterologist

Abstract: StreszczenieWstęp: Wykorzystanie promieniowania rentgenowskiego (rtg.) w gastroenterologii stanowi jeden z licznych podobszarów radiologii interwencyjnej. W gastroenterologii fluoroskopia rtg. jest używana w procedurach terapeutycznych, z których częsta jest endoskopowa cholangiopankreatografia wsteczna (ECPW). Procedura ECPW pokazuje radiologiczny obraz dróg żółciowych i przewodu trzustkowego. Materiał i metody: W ramach niniejszej pracy przeprowadzono ocenę narażenia na promieniowanie rtg. gastroenterologa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…A recent meta‐analysis found that the dose to the lens of the eye was even higher, 18 µSv/procedure for fixed effect analysis and 139 µSv/procedure for random effect analysis. 12 Based on our results and those found in the literature, 11 , 12 , 13 , 14 , 15 approaching or exceeding the annual dose constraint for the lens of the eye may be possible. Thus, the authors recommend that staff within 1m of the patient utilize radioprotective eyewear.…”
Section: Discussionsupporting
confidence: 73%
“…A recent meta‐analysis found that the dose to the lens of the eye was even higher, 18 µSv/procedure for fixed effect analysis and 139 µSv/procedure for random effect analysis. 12 Based on our results and those found in the literature, 11 , 12 , 13 , 14 , 15 approaching or exceeding the annual dose constraint for the lens of the eye may be possible. Thus, the authors recommend that staff within 1m of the patient utilize radioprotective eyewear.…”
Section: Discussionsupporting
confidence: 73%
“…It is well known that frame rate directly correlates with RD and that half pulsed imaging reduces the RD [ 24 ] [ 25 ]. NS1 utilizes half pulsed imaging, and this effect of RD reduction seems to be natural, as described in other reports [ 26 ] [ 27 ]. However, the important point is that NS1 contains some novel technologies that maintain image quality even in a half-frame rate [ 28 ] (S1 video).…”
Section: Discussionmentioning
confidence: 81%
“…The estimated risk associated with exposure to ionizing radiation is based on evaluation of the effective dose (E), starting from the equivalent dose (H) received during X-ray-guided procedures. Concerning endoscopic procedures, risks have been widely studied, with special focus on the potential risk of radiation-induced cancer 1 2 3 4 5 6 7 8 9 .…”
Section: Introductionmentioning
confidence: 99%